0189 Application of a dynamic population-based model to assess the effect of silica exposure interventions on COPD in Dutch construction workers: results from the 'Relieved Working Study'. (23rd June 2014) - Pronk, Anjoeka; Boessen, Ruud; van Deurssen, Erik; Meijster, Tim; Klein Entink, Rinke; van Duuren-Stuurman, Birgit; Heederik, Dick; Warren, Nick; Tan, Emma
Abstract : Objectives: A multidimensional intervention aimed at reducing silica exposure in the Dutch construction industry was performed. The objective of this study was to assess the effect of the achieved reduction in exposure on the burden of chronic obstructive pulmonary disease (COPD) in construction workers. Method: The intervention aimed at technical, organisational and psycho-social factors and was performed in four construction companies. Pre and post intervention respirable quartz exposure measurements were taken in these and four additional control companies. A mathematical simulation model was used to generate COPD prevalences (GOLD stage ≥1) in response to silica exposure, population characteristics and Dutch trends in smoking behaviour for a population of 20–65 year old construction workers with lifetime silica exposure. Results: Pre-intervention exposure assessment demonstrated highest respirable quartz levels (mg/m 3 ) for concrete drillers (GM: 0.20, GSD: 2.75), tuck pointers (GM: 0.18, GSD (2.18) and demolishers (GM: 0.12, GSD: 2.86), exceeding the Dutch occupational exposure limit (OEL) in 71, 92 and 97% of cases, respectively. Preliminary simulations estimated COPD prevalence at 21, 20 and 17% for these groups respectively, as compared to 14% when quartz exposure is reduced to the Dutch OEL and 8% with no exposure. Conclusions: For several job categories high exposure levels exceeding the Dutch OEL were observed. Reducing these levels to below the OEL would lead to a substantial reduction in the burden of disease. The post intervention exposure levels will become available early 2014. The effect on the burden of disease and economic impact will be assessed with an refined model incorporating population dynamics.